MODERN APPROACHES TO THE ORGANIZATION OF TRANSLATIONAL RESEARCH - A. S. Kolbin; R. A. Gapeshin; S. M. Malyshev (Педиатрическая фармакология, 2014)
The growing distance between fundamental science and clinical medicine may bring risk of decreasing effectiveness of biomedical research. Translational research is a relatively new concept; it implies application of fundamental research results to practice (from bench to bedside) using a specific combination of research stages. As a result, it provides integrated information on safety, efficacy and effectiveness of a medical technology. However, there is no generally accepted view on aims and structure of translational research. This review presents analysis of different methodological approaches to translational research.